2008
DOI: 10.1128/aem.00602-08
|View full text |Cite
|
Sign up to set email alerts
|

Growth Temperature Exerts Differential Physiological and Transcriptional Responses in Laboratory and Wine Strains of Saccharomyces cerevisiae

Abstract: Laboratory strains of Saccharomyces cerevisiae have been widely used as a model for studying eukaryotic cells and mapping the molecular mechanisms of many different human diseases. Industrial wine yeasts, on the other hand, have been selected on the basis of their adaptation to stringent environmental conditions and the organoleptic properties that they confer to wine. Here, we used a two-factor design to study the responses of a standard laboratory strain, CEN.PK113-7D, and an industrial wine yeast strain, EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 68 publications
10
81
1
1
Order By: Relevance
“…The combination of comparative microarray data sets with existing models of yeast metabolism and interaction networks offers the potential for in silico evaluation of biologically relevant gene expression changes in the context of key areas of metabolism (16,34). In this study, we demonstrate that differences in gene expression patterns between strains can be linked to phenotypic differences and to specific reporter metabolites around which significant metabolic and physiological changes can be grouped.…”
mentioning
confidence: 91%
“…The combination of comparative microarray data sets with existing models of yeast metabolism and interaction networks offers the potential for in silico evaluation of biologically relevant gene expression changes in the context of key areas of metabolism (16,34). In this study, we demonstrate that differences in gene expression patterns between strains can be linked to phenotypic differences and to specific reporter metabolites around which significant metabolic and physiological changes can be grouped.…”
mentioning
confidence: 91%
“…It has a long history of use in bakeries to raise dough and in the production of alcoholic beverages; it is used to produce pharmaceuticals such as insulin and for fermenting sugars from rice, wheat, barley, corn, and grape juice (Pizarro et al, 2008). In particular, it has been used as an agent of bioethanol production as well as for wine, bread, beer, and sake fermentation (Belloch et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several transcriptomic studies have also been published for research conducted with wine yeast strains (Erasmus et al, 2003;Rossignol et al, 2003;Varela et al, 2005;Mendes-Ferreira et al, 2007;Marks et al, 2008;Pizarro et al, 2008;Rossouw & Bauer, 2008). These studies have illuminated the intrinsic genetic and regulatory mechanisms involved in fermentation, and have greatly increased our understanding of this important process.…”
Section: -Transcriptomicsmentioning
confidence: 99%
“…These studies have illuminated the intrinsic genetic and regulatory mechanisms involved in fermentation, and have greatly increased our understanding of this important process. For instance, Pizarro et al (2008) showed how growth temperature and nitrogen limitation affects differential physiological and transcriptional responses in both laboratory and wine strains of S. cerevisiae. Nitrogen metabolism was found to be deregulated in the wine yeast (allowing simultaneous uptake of different nitrogen sources), which explains the competitive advantage of wine yeast strains in real wine fermentations.…”
Section: -Transcriptomicsmentioning
confidence: 99%